Mycorrhiza : function, diversity, state of the art - Varma, A. 1939-; Prasad, Ram (Professor of microbiology); Tuteja, Narendra (Springer Nature, 2017)
This book is perfectly timed for the worldwide explosion of interest in mycorrhizal research. With a strong emphasis on the latest findings in genetics and molecular biology, it contains all current information and speculation on the structure, function and biotechnological applications of mycorrhizas.